A comparison of non-violent, psychologically violent, and physically violent male college daters - Lundeberg, K. L.; Stith, Sandra M.; Ward, D. B.; Penn, C. E. (My University, 2012)
This brief report explores dating violence by comparing three groups of male college students (non-abusive, psychologically abusive only, and physically abusive). These men were compared on measures of impulsivity, problems with alcohol, life satisfaction, anger management skills, history of witnessing abuse, history of experiencing abuse, and relationship satisfaction. Data for this analysis were obtained from a sample of 115 male college students. Differences between the three groups of men were found in the levels of problems with alcohol, relationship satisfaction, and anger management skills. Anger management skills best differentiated the three groups of men, leading to the conclusion that dating violence prevention and intervention strategies with male college students should address anger management skills.
Keywords: Dating violence; Psychological abuse; Physical abuse; Anger management